2017
DOI: 10.1007/s00204-017-1935-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of human sulfotransferase 1A1 and N-acetyltransferase 2 in the metabolic activation of 16 heterocyclic amines and related heterocyclics to genotoxicants in recombinant V79 cells

Abstract: Heterocyclic aromatic amines (HAAs) are primarily produced during the heating of meat or fish. HAAs are mutagenic and carcinogenic, and their toxicity in model systems depend on metabolic activation. This activation is mediated by cytochrome P450 (CYP) enzymes, in particular CYP1A2. Some studies have indicated a role of human sulfotransferase (SULT) 1A1 and N-acetyltransferase (NAT) 2 in the terminal activation of HAAs. In this study, we conducted a metabolism/genotoxicity relationship analysis for 16 HAAs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 42 publications
3
21
0
2
Order By: Relevance
“…The results differed with the heterocyclic amine carcinogen tested, as rapid acetylator NAT2*4 did not affect levels of mutagenesis and DNA adduct formation following incubation with PhIP (Metry et al 2007) whereas both mutagenesis and DNA adduct formation were markedly higher in CHO cells possessing rapid acetylator NAT2*4 following incubation with IQ or MeIQx (Metry et al 2010). The conclusion that NAT2 is necessary for the DNA damage and mutagenesis induced by MeIQx and IQ but not PhIP was recently confirmed in V79 Chinese hamster cells (Chevereau et al 2017). Our laboratory also reported higher levels of ABP-induced hprt mutants and DNA adducts in DNA repair-deficient CHO cells transfected with CYP1A1 and NAT2*4 ).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…The results differed with the heterocyclic amine carcinogen tested, as rapid acetylator NAT2*4 did not affect levels of mutagenesis and DNA adduct formation following incubation with PhIP (Metry et al 2007) whereas both mutagenesis and DNA adduct formation were markedly higher in CHO cells possessing rapid acetylator NAT2*4 following incubation with IQ or MeIQx (Metry et al 2010). The conclusion that NAT2 is necessary for the DNA damage and mutagenesis induced by MeIQx and IQ but not PhIP was recently confirmed in V79 Chinese hamster cells (Chevereau et al 2017). Our laboratory also reported higher levels of ABP-induced hprt mutants and DNA adducts in DNA repair-deficient CHO cells transfected with CYP1A1 and NAT2*4 ).…”
Section: Introductionsupporting
confidence: 53%
“…Similar findings have been reported following administration of heterocyclic amines MeIQx and IQ (Metry et al 2010) but not PhIP (Metry et al 2007). More recently, it was confirmed that transfection of human NAT2 into V79 Chinese hamster cells increases mutagenicity of MeIQx and IQ, but not PhIP (Chevereau et al 2017).…”
Section: Discussionmentioning
confidence: 89%
“…The In‐Cell Western technique was performed as previously described [Graillot et al, ; Khoury et al, ,b; Chevereau et al, ]. Briefly, after the treatment, cells were fixed with 4% paraformaldehyde (Electron Microscopy Science) in phosphate buffered saline (PBS) and permeabilized with 0.2% Triton X‐100.…”
Section: Methodsmentioning
confidence: 99%
“…LOAEC (Lowest Observed Adverse Effect Concentration) parameter for each metalloid was based on the first concentration for which we observed genotoxicity. Genotoxicity was considered positive only if three criteria were all fulfilled: (1) The compound caused a 1.3‐fold increase in γH2AX, (2) there was a statistically significant difference compared to controls and (3) a level of cytotoxicity below 50% of the controls was observed [Graillot et al, ; Khoury et al, ,b; Chevereau et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…Among them, furanocoumarins showed the strongest antimutagenic effects in the Ames test. It is important to note that furanocoumarins were well known Cytochrome P450 (CYP) 1A2 inhibitors [45], and the mutagenicity of Trp-P-1 and PhIP depends on their bioactivation by CYP 1A2 [46]. These facts suggest that one of the mechanisms of the antimutagenic effects of furanocoumarins against Trp-P-1 and PhIP may be the inhibition of the CYP 1A2 enzyme.…”
Section: Discussionmentioning
confidence: 99%